PELAYANAN SISTEM KOMPUTERISASI HAJI TERPADU (SISKOHAT) DALAM MENGARAHKAN TERTIB ADMINISTRASI CALON JAMAAH HAJI - Khairul, Atika; Bahrudin, Bahrudin; Hilman, Fathin Anjani; Dasir, Khoirizi H. (Mabrur: Academic Journal of Hajj and Umra, 2023)
This study aims to investigate, find out the supporting and inhibiting factors of SISKOHAT services in directing the orderly administration of prospective hajj pilgrims at the Ministry of Religion of Sumedang Regency in 2023. The theory used in this study is the Service theory according to Sampara. This study uses a qualitative method. The results of the study show that SISKOHAT provides convenience in managing hajj administration through aspects of reliability, responsiveness, assurance, empathy, and tangible service. Supporting factors include adequate equipment, trained workers, efficiency, accuracy, centralized management, improved services, and data security. While the inhibiting factors are unstable connections or networks, poor central systems, and lack of technical discipline in system management.